Salir del desierto. El relevo misional del primer grupo de dominicos en la península de Baja California (1788-1795) - Chávez Moreno, Wilfredo (2016)
The article tackles how occurred the relief of the frst group Dominican of the peninsula of Baja California, that goes of 1788 until 1795. The relief became in the moment in which the order of preachers in New Spain went through a crisis, whose effects discerned in the decrease of the number of friars, and the stray of his vicarious houses. The context resulted adverse for the effective relief of Dominican in the missions of the peninsula of Baja California. From 1789 they arrived to the new missioners for the alternation to the ancient.